Debates around the law of Public Education of Bilingual Intercultural Indigenous Community Management in Chaco (Praxis Educativa, 2015)
This paper analyzes and discusses the Law Nº 7446 named “Educación Pública de Gestión Comunitaria Bilingüe Intercultural Indígena” (Public Management Community Bilingual Intercultural Indigenous Education) approved in the Chaco province in 2014. Specifically reviews the discussions on the name of these Schools: Gestión Social (Social Management) and Gestión Comunitaria (Community Management). It also analyzes the involvement of the Community Council in the designation of the educational staff. The data used for this paper is: different versions of the Project Law, regional news press between 2010 and 2014, official speeches and some interviews with the people involved in this educational process (Union Educational Leaders and native teachers). This paper concludes thinking on the meanings of interculturality notion observed in the speeches of the social actors involved in Indigenous Education.
Keywords: legislation; education; indigenous; Chaco; interculturality